ENHANCING MOTIVATION IN LEARNING ENGLISH: STUDENTS IN PRIMARY SCHOOL - Hayu Dian Yulistianti (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2016)
Motivation is the most important factor for educator in order to improve learning. A number of teachers have contributed their study how to enhance student??s motivation. It is one of the most important targets in daily basis. Conceptualized student??s learn, work effectively, drive to engage and energy, and achieve students?? potential at school. This paper describes the characteristics of primary students, the role of primary English teacher and focuses on the strategies of the teachers to motivate children to learn English. There are three ways to motivate children: achieving intrinsic, extrinsic and group motivation. In achieving intrinsic motivation, it is concluded that TPR, using songs and playing games are good strategies for children. Whereas, achieving extrinsic motivation, from the weakest to the strongest degree, extrinsic motivation is classified into ??external regulation, interjected regulation and identified regulation??. And the last is group motivation, group motivation plays a very important role in language teaching which occurs in the classroom. So it is wise for primary school English teachers to create an active motivational atmosphere where children feel secure to learn.